IFlowPlate—A Customized 384‐Well Plate for the Culture of Perfusable Vascularized Colon Organoids. Issue 46 (1st October 2020) - Rajasekar, Shravanthi; Lin, Dawn S. Y.; Abdul, Lyan; Liu, Amy; Sotra, Alexander; Zhang, Feng; Zhang, Boyang
Abstract: Despite the complexity and structural sophistication that 3D organoid models provide, their lack of vascularization and perfusion limit the capability of these models to recapitulate organ physiology effectively. A microfluidic platform named IFlowPlate is engineered, which can be used to culture up to 128 independently perfused and vascularized colon organoids in vitro. Unlike traditional microfluidic devices, the vascularized organoid‐on‐chip device with an "open‐well" design does not require any external pumping systems and allows tissue extraction for downstream analyses, such as histochemistry or even in vivo transplantation. By optimizing both the extracellular matrix (ECM) and the culture media formulation, patient‐derived colon organoids are co‐cultured successfully within a self‐assembled vascular network, and it is found that the colon organoids grow significantly better in the platform under constant perfusion versus conventional static condition. Furthermore, a colon inflammation model with an innate immune function where circulating monocytes can be recruited from the vasculature, differentiate into macrophage, and infiltrate the colon organoids in response to tumor necrosis factor (TNF)‐ inflammatory cytokine stimulation is developed using the platform. With the ability to grow vascularized colon organoids under intravascular perfusion, the IFlowPlate platform could unlock new possibilities for screening potential therapeutic targets or modeling relevant diseases. Abstract : In recent years, there has been significant interest in organoid systems for biological modeling. However, organoids usually lack vascularization and are cultured under static conditions. In this work, a customized 384‐well plate platform is developed, named IFlowPlate, which can be used to vascularize and perfuse organoids readily. This is the first system that has demonstrated organoid vascularization with intravascular perfusion.